2021
DOI: 10.3389/fphar.2021.773660
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of the Role of Anthocyanins on Bone Regeneration

Abstract: Bone regeneration in osteoporosis and fragility fractures which are highly associated with age remains a great challenge in the orthopedic field, even though the bone is subjected to a continuous process of remodeling which persists throughout lifelong. Regulation of osteoblast and osteoclast differentiation is recognized as effective therapeutic targets to accelerate bone regeneration in osteopenic conditions. Anthocyanins (ACNs), a class of naturally occurring compounds obtained from colored plants, have rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 79 publications
2
14
0
1
Order By: Relevance
“…At this age, bone formation still plays a significant role in bone remodeling through interplay with bone resorption. Recent research has identified delphinidin-3-rutinoside, a major anthocyanin (44%) in blackcurrant [ 30 ], affects osteoblast differentiation by activating the fibroblast growth factor (FGF) pathway [ 34 ], demonstrating its potential as a bone stimulating agent for the prevention of PMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this age, bone formation still plays a significant role in bone remodeling through interplay with bone resorption. Recent research has identified delphinidin-3-rutinoside, a major anthocyanin (44%) in blackcurrant [ 30 ], affects osteoblast differentiation by activating the fibroblast growth factor (FGF) pathway [ 34 ], demonstrating its potential as a bone stimulating agent for the prevention of PMO.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, six months of blackcurrant supplementation led to a significant increase in serum P1NP, especially in the high-dose group. Furthermore, although the trends were non-significant, blackcurrant supplementation showed a tendency to mitigate decreases in BALP, OC, and the BALP/CTX1 ratio while reducing sclerostin, an important mechanosensor that inhibits osteoblastic bone formation [ 34 ]. We also found that the bone protective effects of blackcurrant supplementation might be different by the degree of progression of postmenopausal bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…For example, quercetin is a suitable source for the odontogenic differentiation of dental pulp stem cells by increasing alkaline phosphatase (ALP) activity and the expression of dentin sialophosphoprotein [ 26 , 27 ]. Other classes of naturally occurring compounds, such as anthocyanins, have great osteogenic effects in healing bone disorders by upregulating osteoblastic genes, promoting the proliferation of osteoblasts, enhancing mineral nodule formation, and protecting against bone mass loss in osteopenic conditions [ 28 ]. Retinoic acid and ascorbic acid, as natural sources of antioxidants, have also shown a significant osteoblastic effect on human dental pulp mesenchymal stem cells.…”
Section: Antioxidant Materialsmentioning
confidence: 99%
“…Several plant-derived components obtained from plant extracts proved their ability to affect the proliferation and differentiation potential of MSCs having as target various signal transduction pathways showing an osteopromotive role in bone regeneration [48,[56][57][58]. The mechanism of action of some bioactive compounds are highlighted in Table 1.…”
Section: Phytocompounds Used In the Bone Regeneration Process -State ...mentioning
confidence: 99%